Pemodelan Geographically Weighted Regression (GWR) dalam Prevalensi Obesitas Dewasa Kabupaten/Kota di Indonesia Tahun 2018 - Prana, Fadhil Aqsa; Khairunnisa, Sherina Rafidah; Puspitasari, Dwi Ajeng; Mahendra, Yusa Okta; Pradastika, Kinanthi Ilham; Budiasih, Budiasih (Seminar Nasional Official Statistics, 2023)
The results of Basic Health Survey show that the prevalence of adult obesity in Indonesia among people over 18 years of age has doubled from 10.5% in 2007 to 21.8% in 2018. We use data the prevalence of adult obesity as dependent variable and 10 independent variables of socio-economic, food security, and obesity-related risk factors in each regencies/cities in Indonesia. The results showed that there was spatial heterogeneity in prevalence of adult obesity in 514 regencies/cities in 2018. Using Geographically Weighted Regression (GWR), consumption of fatty foods had a positive effect on prevalence of adult obesity in all regions, in contrast to the average length of schooling, consumption of vegetables and soft drinks which only had effect in 501, 448, and 425 regencies/cities. Meanwhile, the poverty percentage, Food Security Index, consumption of instant noodles, and physical activity have a negative effect in 509, 458, 331, and 257 regencies/cities in Indonesia.